2020
DOI: 10.1080/17482631.2020.1811533
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating cancer preventative health behaviours and adapting to motherhood: the role of technology in supporting positive health behaviours

Abstract: Purpose: Across the UK and USA, postpartum smoking relapse rates are high, and rates of breastfeeding and physical activity are low. This project aimed to explore these interrelated health behaviours and technology use, for intervention development to support postpartum cancer prevention. Methods: Focus groups and interviews with 26 purposively selected women (15 in Vermont, USA and 11 in Norfolk, UK). Recruitment was from deprived areas experiencing multiple disadvantage. Qualitative data were thematically an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Participants’ postpartum mental and physical health was perceived to be worse than pre-pregnancy 25. Challenges included depression,26 38 healing or managing pregnancy complications,25 49 caesarean section,26 38 child ill-health,41 46 processing being a mother,41 46 49 and loneliness (for overseas-born women) 33. Recovery time after delivery31 44 and support was deemed necessary to address these issues 35 41 42 46.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants’ postpartum mental and physical health was perceived to be worse than pre-pregnancy 25. Challenges included depression,26 38 healing or managing pregnancy complications,25 49 caesarean section,26 38 child ill-health,41 46 processing being a mother,41 46 49 and loneliness (for overseas-born women) 33. Recovery time after delivery31 44 and support was deemed necessary to address these issues 35 41 42 46.…”
Section: Resultsmentioning
confidence: 99%
“…This included improvements in energy levels,36 37 42 mood,42 48 stress42 48 and motivation 42. However, perceived capabilities in initiating and maintaining behaviour change were also related to fatigue29 32 33 36 37 40 42 50 and stress39 49 50 as well as pelvic floor dysfunction40 42 and breastfeeding needs 39 41 42 51. For overseas-born women, consuming culturally valued high calorie foods assisted in the promotion of breastfeeding, recovery and homesickness 33.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies identified in this review used a retrospective study design, but the SVI may be utilized as a stratification tool for prospective studies. For instance, the SVI could be applied to measure the equity of patient recruitment for studies/trials in terms of SDOH [60].…”
Section: Discussionmentioning
confidence: 99%